PERSEPSI MASYARAKAT TERHADAP PROGRAM PEMBERIAN MAKANAN TAMBAHAN (PMT) PEMULIHAN BAGI BALITA STUNTING : KAJIAN STUDI KASUS - Maywati, Sri; Hidayanti, Lilik; Saraswati, Dian (Jurnal Kesehatan Komunitas Indonesia, 2025)
Many various of things was be done to improve the nutritional status of toddlers with stunting, one of which is complementary feeding (PMT) for recovery. However, an evaluation is needed in the form of parental responses to the PMT recovery program to assess the sustainability of the program. This study aims to capture the perceptions/responses of parents who have stunted toddlers who receive the PMT recovery program. The research method is descriptive qualitative with a case study approach. The research informants were parents who had 5 stunted toddlers and health workers as managers of the stunting management program. Data were analyzed descriptively and presented as a series of information in the form of narratives. The results of the study showed good perceptions/responses from parents who had stunted toddlers towards the provision of PMT recovery. Parents felt helped by the existence of PMT recovery to improve the health of their toddlers. In addition to receiving PMT, parents also received education about stunting and improving the health of toddlers so that they grow and develop well, which was carried out by health center officers. Suggestions were given to parents not to rely on the PMT recovery program and to choose local food ingredients that are more affordable for nutritious food intake for stunted toddlers.